Role of Phosphoinositide 3-OH Kinase p110β in Skeletal Myogenesis - Matheny, Ronald W. (Mol Cell Biol, 2015)
Phosphoinositide 3-OH kinase (PI3K) regulates a number of developmental and physiologic processes in skeletal muscle; however, the contributions of individual PI3K p110 catalytic subunits to these processes are not well-defined. To address this question, we investigated the role of the 110-kDa PI3K catalytic subunit β (p110β) in myogenesis and metabolism. In C2C12 cells, pharmacological inhibition of p110β delayed differentiation. We next generated mice with conditional deletion of p110β in skeletal muscle (p110β muscle knockout [p110β-mKO] mice). While young p110β-mKO mice possessed a lower quadriceps mass and exhibited less strength than control littermates, no differences in muscle mass or strength were observed between genotypes in old mice. However, old p110β-mKO mice were less glucose tolerant than old control mice. Overexpression of p110β accelerated differentiation in C2C12 cells and primary human myoblasts through an Akt-dependent mechanism, while expression of kinase-inactive p110β had the opposite effect. p110β overexpression was unable to promote myoblast differentiation under conditions of p110α inhibition, but expression of p110α was able to promote differentiation under conditions of p110β inhibition. These findings reveal a role for p110β during myogenesis and demonstrate that long-term reduction of skeletal muscle p110β impairs whole-body glucose tolerance without affecting skeletal muscle size or strength in old mice.